Historical Process and its Theoretical Reconstructions - Jurkūnaitė, Gema (Problemos, 1986)
Two views can be singled out concerning historical knowledge, namely, the one considering history as a sequence of particular events, the other considering it as a pro cess, comprising different stages. The first view in the end leads to relativism. The latter in its extreme form results in the conclusion that not only every age has its own history, but even every historian has it. The materialistic conception of history as of a process characterized by definite economic structures provides objective criteria for the evaluation of the progressiveness of classes as well as criteria for the selection of historical data.